ANALISIS HAMBATAN PEMBELAJARAN BIOLOGI PADA PELAKSANAAN KURIKULUM MERDEKA - Usman, Usman; Lestari, Iing Dwi; Astuti, Sri Handayani; Izanah, Nova; Wardani, Rizka Ardya; Rahmah, Arina; Purbasari, Nurindah (Transpublika Publisher, 2023)
The Merdeka Curriculum is a curriculum that has been inaugurated since the 2021/2022 school year and will be applied to the national curriculum in the 2022/2023 school year. This curriculum is set as a form of learning recovery due to the Covid-19 pandemic which is one of the causes of students experiencing learning lags. In the implementation of the Merdeka Curriculum, there will definitely be obstacles or obstacles, both from internal and external factors. This study aims to find out the obstacles faced by biology teachers of Yuppentek 1 High School in the learning process of the Merdeka Curriculum. The type of research used is descriptive qualitative using two types of research data in the form of primary data obtained by conducting interviews, distributing questionnaires, as well as documentation and secondary data in the form of journals, books, and data from schools. Based on the research that has been carried out, it can be concluded that the obstacles for biology teachers in the implementation of the Merdeka Curriculum at Yuppentek 1 High School are: (i) in the learning process by 21,4% have difficulty determining learning models that are relevant to the Merdeka Curriculum and difficulties in time management, (ii) obstacles to teaching materials are not felt by biology teachers at Yuppentek 1 High School because the teaching materials are adequate, (iii) the process and implementation of the assessment do not experience obstacles because the evaluation materials used have measured the abilities of students, (iv) and finally there are no obstacles in obtaining information about the Merdeka Curriculum, because teachers get enough information with the socialization of the Merdeka Curriculum.